Jitter, noise, and signal integrity at high-speed. - Peng Li, Mike, ....- (Upper Saddle River : Pearson, 2007)
Coverage includes JNB component classification, interrelationships, measurement references, and transfer functions Statistical techniques and signal processing theory for quantitatively understanding and modeling JNB and related components Jitter, noise, and BER: physical/mathematical foundations and statistical signal processing views Jitter separation methods in statistical distribution, time, and frequency domains Clock jitter in detail: phase, period, and cycle-to-cycle jitter, and key interrelationships among them PLL jitter in clock generation and clock recovery Jitter, noise, and SI mechanisms in high-speed link systems Quantitative modeling and analysis for jitter, noise, and SI Testing requirements and methods for links and systems Emerging trends in high-speed JNB and SI As data rates continue to accelerate, engineers encounter increasingly complex JNB and SI problems. In Jitter, Noise, and Signal Integrity at High-Speed, Dr. Li provides powerful new tools for solving these problems-quickly, efficiently, and reliably.